2020
DOI: 10.3390/molecules25040842
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Chelidonium majus Extract and Its Alkaloids on LPS-Stimulated Cytokine Secretion in Human Neutrophils

Abstract: Due to certain differences in terms of molecular structure, isoquinoline alkaloids from Chelidonium majus engage in various biological activities. Apart from their well-documented antimicrobial potential, some phenanthridine and protoberberine derivatives as well as C. majus extract present with anti-inflammatory and cytotoxic effects. In this study, the LC–MS/MS method was used to determine alkaloids, phenolic acids, carboxylic acids, and hydroxybenzoic acids. We investigated five individually tested alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…The aerial parts of this plant consist of isoquinoline alkaloids (berberine, chelerythrine, chelidonine, coptisine, sangui-narine, and stylopine), whereas herbs of C. majus consist of carotenoids, flavonoids, organic acids, and proteins [ 2 , 3 , 4 , 5 , 6 , 7 ]. The extract of C. majus has various antioxidant properties (elimination of reactive oxygen species (ROS), and protection from oxidative stress), with a wide range of medicinal properties such as analgesic, anti-inflammatory, antimicrobial, anti-spasmodic, antitumor, antiviral, choleretic, and hepatoprotective properties [ 1 , 2 , 5 , 8 , 9 , 10 , 11 , 12 ]. It has also been used for the treatment of asthma, cancer, chronic bronchitis, eczema, gastrointestinal diseases, liver disorder, oral infection, pain and nervous disorders, ringworm, and ulcer [ 5 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aerial parts of this plant consist of isoquinoline alkaloids (berberine, chelerythrine, chelidonine, coptisine, sangui-narine, and stylopine), whereas herbs of C. majus consist of carotenoids, flavonoids, organic acids, and proteins [ 2 , 3 , 4 , 5 , 6 , 7 ]. The extract of C. majus has various antioxidant properties (elimination of reactive oxygen species (ROS), and protection from oxidative stress), with a wide range of medicinal properties such as analgesic, anti-inflammatory, antimicrobial, anti-spasmodic, antitumor, antiviral, choleretic, and hepatoprotective properties [ 1 , 2 , 5 , 8 , 9 , 10 , 11 , 12 ]. It has also been used for the treatment of asthma, cancer, chronic bronchitis, eczema, gastrointestinal diseases, liver disorder, oral infection, pain and nervous disorders, ringworm, and ulcer [ 5 , 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the cytotoxicity against stomach- and liver-derived cells may be associated with an inflammatory response manifested by cytokine expression and release. In our previous study on lipopolysaccharide-stimulated human neutrophils [ 57 ], we found that several alkaloids (sanguinarine, berberine, chelidonine, and chelerythrine) contained in the extracts from both tested plants [ 56 ], depending on the specific concentrations, had a dual anti-inflammatory and pro-inflammatory effect. Hence, the inflammatory response of stomach and liver cells and tissues upon treatment with the antibacterial extracts should be considered in future studies, including in vivo models.…”
Section: Resultsmentioning
confidence: 99%
“…The plant is a rich source of protoberberine alkaloids such as berberine, dihydroberberine, coptisine, sanguinarine, and protopine. Several recent reports have indicated that coptisine and sanguinarine have various biological activities and show anti-proliferative properties [ 27 ]. In our recent studies, we showed that some of these compounds (berberine and coptisine) can act synergistically; thus, the multi-component composition of these extracts may significantly increase their pharmaceutical activity.…”
Section: Discussionmentioning
confidence: 99%